PERGESERAN MAKNA “BORU NI RAJA” BAGI PEREMPUAN BATAK TOBA (Studi tentang Perempuan Batak Toba di Desa Buatan Besar Kecamatan Siak Kabupaten Siak Provinsi Riau) - Debora Hutagalung; Bedriati Ibrahim; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack : Boru ni Raja is an honor and respect for every Batak woman who started since she was born into the world. The purpose of this paper is 1) to find out the true meaning of "boru ni raja" in the customs of the Toba Batak community, 2) to find out the life of Toba Batak women as a "boru ni raja", 3) to find out the perception of Toba Batak women in Buantan Village Big Siak District, Siak Regency, Riau Province about the meaning of "boru ni raja", 4) to find out the implementation of the meaning of "boru ni raja" in the customs of the Toba Batak community in the Village of Large Buantan, Siak District, Siak Provention Regency, Riau. The author uses historical methods, namely heuristics, criticism, interpretation, and historiography, and qualitative methods with data analysis techniques using descriptive qualitative analysis. In collecting data, the researcher uses interview, observation and documentation techniques. The Toba Batak community has a perception that the Boru ni Raja concept is still important to be instilled in every Toba Batak woman and is still suitable to run into modern times today. Along with the development of the times and the many Toba Batak people who live to migrate so that it influences the mindset and perspective of the Batak people. Toba about the position of Toba Batak women as Boru ni Raja. This change in perspective also ultimately affected aspects of the lives of Toba Batak women. This aspect of life can be seen that they have begun to be taken into account in the midst of family, community, and other aspects. Therefore, the Toba Batak women in the Buantan Besar Village continue to hold the meaning of Boru ni Raja in the aspect of lifeKeywords: Boru ni Raja, meaning, shift